2020
DOI: 10.1038/s41598-020-75611-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between job burnout and somatic diseases: a network analysis

Abstract: Job burnout, characterized by feelings of exhaustion, cynicism and reduced personal efficacy, has been defined as a risk state for the development of diseases, but its association with somatic diseases is underexplored. Study participants were 5671 respondents (mean age 44.1 years, range 18–70; 38.6% men) to an online survey of job burnout, using a mobile health web application. Respondents provided data on sociodemographic characteristics, symptoms of burnout, measured with the Maslach Burnout Inventory-Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 27 publications
1
26
0
7
Order By: Relevance
“…A study of the relationship between job burnout and somatic diseases found that there is a significant association between hypertension and burnout and explained this relation to increase the sympathetic activity and the inflammation process. [30] A significant association of neuropsychiatric diseases and taking antipsychotic drugs with low scores on personal achievement. For taking antipsychotic drugs, there are also high scores on EE and DP (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A study of the relationship between job burnout and somatic diseases found that there is a significant association between hypertension and burnout and explained this relation to increase the sympathetic activity and the inflammation process. [30] A significant association of neuropsychiatric diseases and taking antipsychotic drugs with low scores on personal achievement. For taking antipsychotic drugs, there are also high scores on EE and DP (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by a feeling of insufficient energy or exhaustion, increased mental distance from one's work, or a feeling of negativity or cynicism about one's work and reduced professional efficiency [ 1 ]. The development of burnout syndrome (burnout) can be manifested through psychological and somatic symptoms, such as constant irritability, anxiety, insomnia, forgetfulness, problems with concentration, depression, arrhythmia, hypertension, gastrointestinal problems, and headaches [ 2 , 3 , 4 , 5 ]. As these symptoms are unspecific, burnout is usually unrecognized at the early stages [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, esta análise mostrou graficamente a magnitude da relação entre as variáveis identificadas na técnica de aprendizado de máquina. Outro estudo que utilizou esse tipo de análise mostrou a associação da exaustão emocional elevada à hipertensão arterial e outras doenças crônicas, 6 mesmo fora do período de pandemia.…”
Section: Discussionunclassified
“…Por meio de análise de rede e regressão logística, o estudo mostrou a associação de alta exaustão emocional com hipertensão arterial e outras doenças crônicas após ajuste para idade, sexo, escolaridade e sintomas depressivos. 6 Outra revisão sistemática com 12 estudos avaliando o burnout em PS que trabalham ou não nas enfermarias de COVID-19 da linha de frente mostrou resultados controversos. 7 Dois dos estudos relataram níveis mais altos de fadiga emocional em mulheres em comparação com homens e que o sexo feminino foi um fator de risco para burnout entre profissionais de terapia intensiva.…”
Section: Introductionunclassified